Cocaine and metabolite concentrations in DBS and venous blood after controlled intravenous cocaine administration. (September 2015) - Ellefsen, Kayla N; da Costa, Jose Luiz; Concheiro, Marta; Anizan, Sebastien; Barnes, Allan J; Pirard, Sandrine; Gorelick, David A; Huestis, Marilyn A
Background: DBS are an increasingly common clinical matrix.Methods & results: Sensitive and specific methods for DBS and venous blood cocaine and metabolite detection by LC–HRMS and 2D GC–MS, respectively, were validated to examine correlation between concentrations following controlled intravenous cocaine administration. Linear ranges from 1 to 200 µg/l were achieved, with acceptable bias and imprecision. Authentic matched specimens' (392 DBS, 97 venous blood) cocaine and benzoylecgonine concentrations were qualitatively similar, but DBS had much greater variability (21.4–105.9 %CV) and were lower than in blood.Conclusion: DBS offer advantages for monitoring cocaine intake; however, differences between capillary and venous blood and DBS concentration variability must be addressed.